Food security in the United Arab Emirates: External cereal supply risks - Beshir M. Ali; Ioannis Manikas; Balan Sundarakani (Cogent Economics & Finance, 2022)
The coronavirus pandemic and the Russian invasion of Ukraine have exposed the vulnerability of the food systems of import-dependent countries to supply chain disruptions. This study measured the short-term external cereal supply risks for the United Arab Emirates (UAE) by applying the Herfindahl-Hirschman Concentration Index (HHI) and the Shannon-Wiener Diversity Index (SWI) during 2012-2020. We measured the security of UAE's external cereal supplies by taking the degree of UAE's cereal import dependency, the level of political- and business-related risks of UAE's cereal supplying countries, and the distance between UAE and its supplying countries into account. The results of the index values generally imply that UAE's cereal external supply risk has been low during the sample period. However, the external wheat supply risk has increased since 2017. This was mainly attributable to UAE's increasing dependence on less secured countries, i.e. countries with higher levels of risk assessment values such as Russia. UAE has heavily been dependent on one or two, mostly price competitive, sources for its cereal imports, which also raises the external cereal supply risk. The UAE's increasing dependence on Russia as the main source of cereals and the increasing consolidation of sources pose a serious threat to sustaining food security.
Keywords: 330; Cereals; COVID-19; food security; import dependency; risk; United Arab Emirates